PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM AKUNTANSI KEUANGAN DAERAH, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Pasaman Bara - Suci Rahmadani; Kamaliah Kamaliah; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research aimed to know the influence human resources competence, implementation of local financial accounting system,the use of information technology and the internal control system that affect the quality of local government financial reports. The population of this research is accounting/financial division in SKPD Kabupaten Pasaman Barat and each SKPD 3 respondent. This research used purposive sampling method to taking the sample. The method of collecting the data is using questioner and literature studi. Data collecting the analisysis used multiple regression testing t with the aid SPSS software. The result of research indicated that human resources competence, implementation of local financial accounting, used of information technology, and internal control system have an effect to quality of local government financial reporting. For the government agency can be improved the quality of credibility of financial organizing with utilization of human resources competence, implementation of local financial accounting, information technology be optimum and internal control systemdesign availiability which are produce financial region government reported is quality.Keywords: competence, local financial accounting, information technology, internal control, and government